Wayang: Indonesia’s Cultural Legacy Animating Mythology and Epic Tales - Line Aritasbi Parsial; Anggita Maharani (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2025)
This article examines wayang as an Indonesian cultural heritage that brings mythology and epic narratives to life through historical, cultural, and philosophical perspectives, while also exploring young people’s interest in preserving Wayang Banyumas as a distinctive local puppetry tradition. This study employs a qualitative approach with a descriptive–exploratory design. The findings indicate that most respondents possess a basic level of familiarity with Wayang Banyumas, although their direct participation in live performances remains relatively limited. Knowledge of wayang is acquired through various channels, with social environments, educational institutions, and digital media emerging as the dominant agents of cultural transmission, while the influence of the family has gradually declined. In addition, the cultural consumption patterns of younger generations increasingly take place through virtual platforms rather than in situ performances. These findings suggest that interest in Wayang Banyumas among younger generations persists in a latent form and is strongly influenced by the modes and contexts of cultural presentation.